THE ASSOCIATION BETWEEN TRAUMATIC LIFE EXPERIENCES AND MALADAPTIVE DAYDREAMING IN EMERGING ADULTS - Hanif, Sarah; Jaffri, Noreen (Pakistan Journal of Clinical Psychology, 2025)
Objectives: The current study set out to look into the relationship between maladaptive daydreaming and traumatic life experiences. Emerging adults. Design of the Study: Correlational Survey design/comparative study Place and Duration of the Study: Karachi from November 2023 to February 2024 Sample and Method: The sample consisted of 310 Emerging adults ages 18 – 25 (Female =222 & Males = 88) selected through purposive convenient sampling from various universities and other settings. Three scales were used to assess Traumatic experiences, Defense styles and maladaptive daydreaming. Traumatic Experiences Checklist TEC, Maladaptive daydreaming scale MDS and Defense Mechanisms Rating Scale DMRS- 30. The data was collected in-person and was analyzed through IBM SPSS version 22. Results and Conclusion: The results of the analysis revealed that there is a significant positive relationship of Traumatic life experiences with maladaptive daydreaming and defense mechanisms. These findings highlight the need for customized therapies and support programs that concentrate on awareness and processing of traumatic memories by providing a platform to confront repressed pain. The main implication of the study is to add to the body of knowledge about the mechanism of maladaptive daydreaming which is a growing construct at an alarming rate in Pakistan.